Exclusive Breastfeeding and Educational Attainment of Mother Correlate with Stunting Problem in Musi Rawas Regency - Damanik, Hanna DL; Rostika Flora; Zulkifli, Hilda; Mohammad Zulkarnain (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Introduction: Stunting is a growth condition reflected in a height-for-age or length-for-age that is below -2 standard deviations. It is identified by Sustainable Development Goals (SDGs) as a priority objective for global health improvement. Objective: This study aimed to determine the factors that contribute to stunting in children younger than 5 years. Methods: The study adopted a cross-sectional design and a sample of 150 children under the age of 5 whose mothers were the respondents, was selected using the purposive sampling method. Data were collected through questionnaire interviews and anthropometric measurements. Results: The results showed that 28% of children were stunted, with 54.7% being male and 58% not exclusively breastfed. Approximately 60.7% and 57.3% had fathers with a history of smoking and mothers with high education, respectively. The mothers of 74% were unemployed, while 80.7% of the stunted children were from low-income families. Based on statistical analysis, stunting had a significant correlation with a history of exclusive breastfeeding were significantly correlated (p = 0.01) and educational attainment of mothers (p = 0.04). Conclusion: The prevalence of stunting remained high compared to the national norm. The incidence was correlated with the educational attainment of mothers and the duration of exclusive breastfeeding. Therefore, mothers should be educated about the value of exclusive breastfeeding to avoid the condition.